The Shapiro effect in atomchip-based bosonic Josephson junctions - Grond, Julian; Betz, Thomas; Hohenester, Ulrich; Mauser, Norbert J.; Schmiedmayer, Jörg; Schumm, Thorsten (New journal of physics, 2011)
We analyze the emergence of Shapiro resonances in tunnel-coupled Bose-Einstein condensates, realizing a bosonic Josephson junction. Our analysis is based on an experimentally relevant implementation using magnetic double-well potentials on an atomchip. In this configuration, the potential bias (implementing the junction voltage) and the potential barrier (realizing the Josephson link) are intrinsically coupled. We show that the dynamically driven system exhibits significantly enhanced Shapiro resonances which will facilitate experimental observation. To describe the system's response to the dynamic drive, we compare a single-mode Gross-Pitaevskii (GP) description, an improved two-mode (TM) model and the self-consistent multi-configurational time-dependent Hartree equations for bosons (MCTDHB) method. We show that in the case of significant atom-atom interactions, the spatial dynamics of the involved modes has to be taken into account and only the MCTDHB method allows reliable predictions.
Gesehen am 15.07.2022